Bioconvection Maxwell nanofluid flow over a stretching cylinder influenced by chemically reactive activation energy surrounded by a permeable medium - Khan, Arshad; Iqbal, Zahoor; Ahammad, N. Ameer; Sidi, Maawiya Ould; Elattar, Samia; Awad, Somia; Yousef, El Sayed; Eldin, Sayed M (Frontiers in Physics, 2023)
The role of nanofluids in the development of many electronic devices at industrial level is very significant. This investigation, describes the thermal exploration for a bioconvective flow of Maxwell nanoparticles over stretching and revolving cylinder placed in a penetrable medium. The fluid flow is in contact of chemically reactive activation energy. The swirling flow is induced by the stretched rotary cylinder. The magnetic effect of constant strength is practiced to flow system in combination with thermally radiative effects and heat source/sink for controlling the thermal effects upon the flow system. The thermophoretic and Brownian motion characteristics due to nanofluid flow are captured by implementing the Buongiorno model. The central focus in this work is to explore the thermal and mass transfer for the flow problem accompanied by motile microorganism. The governing equations have converted to dimensionless format with similar variables and homotopy analysis method has then applied for solution of resultant equations. It has concluded in this study that, fluid flow decays for escalation in Maxwell, porosity, magnetic parameters, Forchheimer, bioconvection Rayleigh numbers and grow up with the augmenting values of Buoyancy parameter. The increasing values of Brownian motion, thermophoresis and radiation parameters upsurge the thermal profiles and decline the concentration profiles. Moreover, density of motile microorganism declines with augmentation in Peclet and bioconvection Lewis numbers.